2022
DOI: 10.1037/pag0000699
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal associations of pain and cognitive decline in community-dwelling older adults.

Abstract: Pain is inversely associated with cognitive function in older adults, but the effects of pain on cognitive decline are not fully clear. This study examined the associations of baseline pain, pain persistence, and incident pain with changes in cognition across 10 years in a sample of healthy community-dwelling older adults (n = 688; M age = 74, SD = 6.05) from the Advanced Cognitive Training for Independent and Vital Elderly (ACTIVE) trial. While ACTIVE was a four-arm single-blind cognitive training randomized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 88 publications
2
8
0
Order By: Relevance
“…The current study has uncovered that pain was associated with cognitive function, which was in agreement with previous studies showing older adults with chronic pain had an increased risk of cognitive decline 9,10 . Eccleston and Crombez developed the Cognitive‐Affective model of the Interruptive Function of Pain, which illustrated that pain distracted attention and had competing effects on the brain, resulting in chronic declining of cognitive function over time 28 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The current study has uncovered that pain was associated with cognitive function, which was in agreement with previous studies showing older adults with chronic pain had an increased risk of cognitive decline 9,10 . Eccleston and Crombez developed the Cognitive‐Affective model of the Interruptive Function of Pain, which illustrated that pain distracted attention and had competing effects on the brain, resulting in chronic declining of cognitive function over time 28 .…”
Section: Discussionsupporting
confidence: 89%
“…The incidence of pain among nursing home older adults is as high as 83%, which seriously harms their quality of life 8 . It has been reported that pain is a vital factor in cognitive function as a result of individual demands for attention and competition for limited attentional resources 9,10 . A recent review showed that older adults with pain might experience memory deficits, decreased executive function, and lower emotional decision‐making, thus affecting cognitive function 2 .…”
Section: Introductionmentioning
confidence: 99%
“…We divided the pain distribution into no pain, single-site pain, and more than one site of pain (multisite pain). Similar to other observational pain studies ( 25 , 26 ), by combining the pain characteristics assessment reports at the baseline survey and the follow-up survey 4 years later, we further categorized pain status into the following categories: (1) reporting no pain at both baseline survey and follow-up survey (no pain); (2) reporting pain at the same site at both baseline survey and follow-up survey (pain persistence); and (3) reporting pain at baseline survey but no pain at follow-up survey, or reporting no pain at baseline survey but pain at follow-up survey, etc., that did not meet the criteria for the definition of pain persistence (incident pain). We further categorized the distribution of pain as follows: (1) no pain or single-site pain at baseline survey and follow-up survey; (2) a shift from no pain or single-site pain at baseline survey to multisite pain at follow-up survey; (3) multisite pain at both baseline survey and follow-up survey (multisite pain persistence); and (4) and a shift from multisite pain at baseline survey to no pain or single-site pain at follow-up survey.…”
Section: Methodssupporting
confidence: 84%
“…To account for potential confounding factors, 4 models were constructed, yielding odds ratios (ORs) and 95% confidence intervals (95% CIs) with varying covariate adjustments: Model 1 was unadjusted; Model 2 adjusted for gender and age; Model 3 further included residential area, education, and marital status; and Model 4 also incorporated smoking, drinking, comorbidities (hyperglycemia, hypertension, stroke, heart disease, chronic lung disease, asthma, liver disease, emotional and mental disorders, and malignancies), and falls. To investigate the association between pain characteristics over time and sarcopenia status, we used analytic methods similar to those used in other pain studies ( 25 , 26 ). We classified pain status into 3 categories: no pain, incident pain, and pain persistence, and used univariate and multivariate logistic regression models to analyze their association with sarcopenia.…”
Section: Methodsmentioning
confidence: 99%
“…12,[18][19][20][21] In recent years, an increasing number of longitudinal cohort studies with large samples are also available to support this view. [13][14][15]22,23 For example, a cohort study that followed 10,065 older Americans for 12 years reported that persistent pain was associated with accelerated cognitive decline and an increased probability of dementia. 13 Similarly, a prospective longitudinal study recruiting 693 elderly patients in France also reported that the presence of chronic pain was associated with higher cognitive decline in older adults.…”
Section: The Relationship Between Chronic Pain and Cognitive Impairmentmentioning
confidence: 99%